2020
DOI: 10.1111/apa.15282
|View full text |Cite
|
Sign up to set email alerts
|

Propofol in neonates causes a dose‐dependent profound and protracted decrease in blood pressure

Abstract: It is known that awake endotracheal intubation in newborns causes multiple harmful effects. 1-3 Therefore, in 2001 consensus was reached that only in the delivery room and in life-threating situations associated with the unavailability of intravenous access, tracheal intubation should be performed without the use of analgesia or sedation. 4 Almost twenty years later, the most effective and safe premedication strategy in the newborn population is still to be determined. Propofol is considered one of the accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
4
8
0
Order By: Relevance
“…We found a profound and long-lasting decline in blood pressure after propofol and a high incidence of propofol-induced hypotension. 1 These findings are in accordance with other studies. Although some authors indicate this hypotension as permissive, to our opinion evidence on the effects of propofol-induced hypotension and the sudden and long-lasting decline in blood pressure regardless of the existence of hypotension on the short and long term is lacking.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…We found a profound and long-lasting decline in blood pressure after propofol and a high incidence of propofol-induced hypotension. 1 These findings are in accordance with other studies. Although some authors indicate this hypotension as permissive, to our opinion evidence on the effects of propofol-induced hypotension and the sudden and long-lasting decline in blood pressure regardless of the existence of hypotension on the short and long term is lacking.…”
supporting
confidence: 93%
“…We found a profound and long‐lasting decline in blood pressure after propofol and a high incidence of propofol‐induced hypotension 1 . These findings are in accordance with other studies.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In their prospepective study in very preterm neonates, De Kort et al analysed the effects of different propofol starting doses as premedication for endotracheal intubation on blood pressure (1.0 mg/kg (n = 30), 1.5 mg/kg (n = 23) or 2.0 mg/kg (n = 26)). 1 The authors demonstrated that propofol caused a dose-dependent profound and protracted drop in blood pressure which was mainly dependent on the initial propofol starting dose rather than the cumulative propofol dose. Conversely, in their initial analysis, De Kort et al showed that a propofol starting dose of 2.0 mg/kg provided effective sedation in 86% of patients, compared to 13% and 4% of the patients who received a starting dose of 1.5 mg/kg or 1.0 mg/ kg, respectively.…”
Section: Propofol In Preterm Neonatesmentioning
confidence: 99%
“…In their prospepective study in very preterm neonates, De Kort et al analysed the effects of different propofol starting doses as premedication for endotracheal intubation on blood pressure (1.0 mg/kg ( n = 30), 1.5 mg/kg ( n = 23) or 2.0 mg/kg ( n = 26)) 1 . The authors demonstrated that propofol caused a dose‐dependent profound and protracted drop in blood pressure which was mainly dependent on the initial propofol starting dose rather than the cumulative propofol dose.…”
mentioning
confidence: 99%